Population pharmacokinetics of piperacillin in plasma and subcutaneous tissue in patients on continuous renal replacement therapy. (March 2020) - Bue, Mats; Sou, Tomás; Okkels, Anna Sophie L.; Hanberg, Pelle; Thorsted, Anders; Friberg, Lena E.; Andersson, Torben L.; Öbrink-Hansen, Kristina; Christensen, Steffen
Highlights: Population pharmacokinetics of piperacillin in subcutaneous tissue and plasma in patients treated with continuous renal replacement therapy (CRRT). Subcutaneous tissue concentrations were lower than plasma concentrations. If an aggressive target of 100% f T > 4 × MIC ( Pseudomonas aeruginosa, 16 mg/l) is adopted, continuous infusion is needed. Abstract: Objectives: Piperacillin is a β-lactam antimicrobial frequently used in critically ill patients with acute kidney injury treated with continuous renal replacement therapy (CRRT). However, data regarding piperacillin tissue concentrations in this patient population are limited. A prospective observational study was conducted of free piperacillin concentrations during a single 8-h dosing interval in plasma (8 samples) and subcutaneous tissue (SCT) (13 samples), in 10 patients treated with CRRT following piperacillin 4 g given every 8 h as intermittent administration over 3 min. Methods: A population pharmacokinetic model was developed using NONMEM 7.4.3, to simulate alternative administration modes and dosing regimens. SCT concentrations were obtained using microdialysis. Piperacillin concentrations were compared to the clinical breakpoint minimum inhibitory concentration (MIC) for Pseudomonas aeruginosa (16 mg/l), with evaluation of the following pharmacokinetic/pharmacodynamics targets: 50% f T > 1 × MIC, 100% f T > 1 × MIC, and 100% f T > 4 × MIC. Results: SCT concentrations were generally lower than plasma concentrations. For the target of 50% free time ( f T) > 1 × MIC and 100% f T > 1 × MIC, piperacillin 4 g every 8 h resulted in probability of target attainment (PTA) >90% in both plasma and SCT. PTA > 90% for the target of 100% f T > 4 × MIC was only achieved for continuous infusion. Conclusions: Piperacillin 4 g every 8 h is likely to provide sufficient exposure in both plasma and SCT to treat P.aeruginosa infections in critically ill patients on CRRT, given that targets of 50% f T > 1 × MIC or 100% f T > 1 × MIC are adequate. However, if a more aggressive target of 100% f T > 4 × MIC is adopted, continuous infusion is needed.